Arhitectural design for performance - Carando, Patricia (Uporabna informatika (Ljubljana), 2000)
Few aspects of szstem development cause more concern to designers and frustration to users than performance. Most designers believe that they are designing with performance as a primary concern. Why then, are systems deplozed that are significantly slower thet anticipated, sometimes resulting in a complete design ocerhaul to meet performance needs? Experience suggest thet the reasons are two-fold: (1) A failure to focus at an architectural level when designing for performance, (II) An inability to gather requisite performance metrics early enough in the design cycle to affect the development outcome. Yhe paper recommends two approaches that adress these failings: 1) How to focus on total szstem throughput based on Use Case scenarious when designing for performance, and 2) How to create an architectural prototype that is used to gather performance metrics prior to making firm design decisions.
Keywords: arhitektonska oznaka; arhitektonski prototip; predstavitveni sistem; zmogljivost sistema